Transforming Writing Abilities Through Cooperative Learning Interventions at Senior High School - Izza Nurbaladin Muhammad; Anita Triastuti; Ella Wulandari (Institut Agama Islam Negeri (IAIN) Curup, 2026)
This study aims to investigate the effectiveness of cooperative learning in improving the narrative text writing skills of EFL. high school students. A Classroom Action Research (CAR) design following the Kemmis and McTaggart model was employed, consisting of two cycles with two meetings each. The participants were 35 students (8 males and 27 females) from class XI IPA 2 at SMA Ali Maksum Krapyak, Yogyakarta. Data were collected using a writing assessment rubric developed by Jacobs et al. (1981), evaluating content, organization, vocabulary, language use, and mechanics alongside classroom observation sheets. Scores were analysed using descriptive statistics, including mean calculation, KКМ attainment percentage, and improvement percentage formulas, supplemented by qualitative observation data. The results showed a consistent and significant improvement across both cycles: the mean score rose from 61.57 (Cycle 1 pre-test) to 73.29 (Cycle 1 post-test), and further from 75.14 (Cycle 2 pre-test) to 81.71 (Cycle 2 post-test), yielding a total gain of 20.14 points. Qualitative findings also revealed improved student engagement, collaboration, and peer feedback skills. These results confirm that cooperative learning, implemented with structured roles and progressive scaffolding, is an effective strategy for developing writing competence in EFL senior high school classrooms.